Mutational analysis of CYP2C8 in hypertensive patients using denaturing high performance liquid chromatography. - Teh, Lay Kek; Zahri, Mohd. Khiari; Zakaria, Zainul Amiruddin; Ismail, Rusli; Salleh, Mohd. Zaki (Blackwell Publishing Ltd., 2010)
What is known and Objective: CYP2C8 is involved in the cytochrome P450 (CYP) epoxygenase pathway. Arachidonic acid metabolites such as epoxyeicosatrienenoic acids and hydroxyeicosatetrenoic acids, produced may have a role in hypertension. We aimed to develop a medium through-put method for screening samples of known and new mutations of CYP2C8 using denaturing high performance liquid chromatography (DHPLC).